Penerapan Model Pembelajaran Make A Match untuk Meningkatkan Hasil Belajar Belajar IPA Siswa Kelas V Sekolah Dasar - Dea Widaswari; Cahyo Dwi Andita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aims research to improve the science learning outcomes of fifth grade elementary school students through the application of the Make A Match learning model. The research carried out was Classroom Action Research with research subjects 24 fifth grade elementary school students consisting of 11 boys and 13 girls. The data collection techniques used in this research are interviews, observation, documentation and tests. The instrument used is test questions. Data analysis in this research uses qualitative and quantitative descriptive analysis. From the research conducted, it shows that there is an increase that occurs in each cycle carried out. In cycle I, the percentage of learning completeness was 76.19%, after which it was continued in cycle II, the percentage of learning completeness was 87.5%. Thus, it can be concluded that the application of the Make A Match learning model can improve the science learning outcomes of Class V elementary school students. Keywords: Make A Match, Learning Outcomes, elementary school science